Rodinný dům - Kocman, Alois (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Téma bakalářské práce je novostavba rodinného domu v obci Rudice v Moravském krasu. Dům má dvě nadzemní podlaží a je částečně podsklepený. Součástí objektu je garáž pro jeden osobní automobil. Dům je navržen z konstrukčního systému Porotherm. Střecha je šikmá dvouplášťová s dřevěnou nosnou konstrukcí.

The theme of bachelor’s thesis is a detached house in the village Rudice in the Moravian Karst. The house with two floors is partly basement. The garage for a one car is a component of the object. The house is designed of the construction system Porotherm. The roof is oblique and double layer with a wooden load-bearing construction.
Family house
Keywords: Rodinný dům; Family house